Infestations of the coffee berry borer, Hypotenemus hampei (Coleoptera: Scolitydae) in coffee-growing areas of the State of Mexico, Mexico - Pérez Constantino, Aurelio; Ramírez Dávila, José Francisco; Fogueroa Figueroa, Dulce Karen (Revista Colombiana de Entomología, 2023)
Currently, the coffee berry borer (Hypotenemus hampei) is the most economically important pest of coffee cultivation and is present in most of the coffee growing areas of the world. In Mexico it is found in all coffee producing states, in municipalities catalogued as "Zones under phytosanitary control" by the Servicio Nacional de Sanidad, Inocuidad y Calidad Agroalimentaria (National Service of Health, Safety and Agroalimentary Quality). Its attack reduces the harvest yield and affects the quality of the bean. In the state of Mexico since 2017 it had only been reported in one of its eight municipalities with coffee production. In order to detect the presence and distribution of the pest, trapping and sampling of the CBB was carried out on farms in the coffee-growing region in the south of the state of Mexico. As a result, in November 2021 it was found present in a plot in the locality of Rincón del Cristo in the municipality of Sultepec and in March 2022 it was found in the locality of Las Joyas in the municipality of Amatepec. In both municipalities, sampling in previous cycles carried out by the SENASICA coffee program had not detected the presence of the pest. Considering the probable absence of natural enemies, the lack of knowledge of the insect's management and control in the region by coffee growers, the rapid distribution and infestation, and the damage to production and bean yield, it is considered necessary to give priority to this new phytosanitary condition reported in this study.